Systematic Literature Review of Leadership Theories and Styles in Indonesian Organizational Contexts - Amallia, Chairun; Rino; Wardi, Yunia (LifeSciFi, 2025)
In response to rapid organizational change and increasing environmental complexity, leadership has become a critical factor in determining organizational effectiveness. This study conducts a Systematic Literature Review (SLR) to examine the dynamics of leadership theories within the context of Indonesian organizations, a setting characterized by distinctive cultural, social, and institutional values. The review was carried out following a structured SLR procedure consisting of planning, identification, screening, eligibility, and synthesis stages. Articles were selected based on explicit inclusion criteria, including peer-reviewed journal publications, empirical studies focusing on leadership in Indonesian organizational contexts, publications in English or Indonesian, and studies published within a defined time frame. A total of selected studies were systematically analyzed to identify dominant leadership styles, key influencing factors, and their impacts on organizational outcomes such as employee performance, motivation, organizational commitment, and job satisfaction. The findings indicate that transformational, transactional, and culturally embedded leadership styles are most prevalent, with cultural values, organizational structure, and leader–follower relationships playing significant roles. This study contributes by providing an integrative mapping of leadership theories in Indonesia, highlighting contextual challenges and opportunities, and offering clear directions for future research on culturally adaptive and evidence-based leadership development in Indonesian organizations.